Architected Multimaterial Lattices with Thermally Programmable Mechanical Response. (29th September 2021) - Mueller, Jochen; Lewis, Jennifer A.; Bertoldi, Katia
Abstract: Architected materials typically maintain their properties throughout their lifetime. However, there is growing interest in the design and fabrication of responsive materials with properties that adapt to their environment. Toward this goal, a versatile framework to realize thermally programmable lattice architectures capable of exhibiting a broader range of mechanical responses is reported. The lattices are composed of two polymeric materials with disparate glass transition temperatures, which are deterministically arranged via 3D printing. By tailoring the local composition and structure, architected lattices with tunable stiffness, Poisson's ratio, and deformation modes controlled through changes in the thermal environment are generated. The platform yields lightweight polymer lattices with programmable composition, architecture, and mechanical response. Abstract : A generalized framework for programming multimaterial lattices is reported. By co‐printing thermally active and passive materials on triangular lattices, architectures that can fundamentally change their stiffness, Poisson's ratio, and deformation mode are created.